Meningkatkan Kompetensi Wirausaha Siswa SMK melalui Pelatihan BMC - Sholahuddin, Muhammad; Ngafwan; Effendy, Marwan; Wajdi, Muhammad Farid; Surono, Arif (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
students for the dynamic global world. Research shows a positive relationship between entrepreneurship education, entrepreneurial activities, and entrepreneurial intentions of vocational students. The integration of entrepreneurship education in the vocational education system supports the national agenda to encourage innovative and entrepreneurial practices among youth. In this context, the development of entrepreneurial skills among SMK students is essential, including communication, collaboration, and digital skills. The 2019 National Standard for Vocational Education emphasizes the importance of entrepreneurship, character, and literacy competencies. Business Model Canvas (BMC) training is a solution to help SMK students understand and plan their business comprehensively, improve their readiness to create jobs and overcome obstacles in starting a business. The study involved 30 students of SMKN 1 Gantiwarno, Klaten, and was organized at Universitas Muhammadiyah Surakarta using lecture, demonstration, and discussion methods. The result was an increase in students' knowledge, skills, and abilities in planning a business with BMC. This activity successfully benefited the Perempuan Indonesia Maju community and the vocational school students. It is desired that students can apply the knowledge gained and it is recommended to organize follow-up training to deepen the material and understanding. Continuous evaluation will ensure the long-term impact of this community service.